Effect of Cognitive Behaviour Therapy on Stress Reduction among Fine and Applied Arts Trainee Instructors in Colleges of Education in South-East, Nigeria - Chinweoke Onwuasoanya, Francisca; Foster Emefesi, Chidi; Doris Edumchieke Ubah, Rita; Kenechukwu Nwachukwu, Udeaja; Ezema Appolonia, Ngozi; Joecollins Chiemezie, Ezepue (International Journal of Psychosocial Rehabilitation, 2021)
Fine and Applied Arts Trainee Instructors is the engine house of fast-tracking socio-cultural development. But the effect of stress may bring about significant underperformance among Fine and Applied Arts Trainee Instructors. Such underperformance may in the long run result in national underdevelopment and acute infrastructural deficit as experienced among countries of the World, Nigeria inclusive. In respect to this, this research seeks to understand the effect of Cognitive Behaviour Therapy on stress reduction among Fine and Applied Arts Trainee Instructors of colleges of education in South-East, Nigeria. A quasi-experimental (pretest, posttest and follow-up) research design was employed. Samples of 100 participants were chosen for the study by selecting 20 Fine and Applied Arts Trainee Instructors each from the five states of South-East using convenient sampling technique. The participants were exposed to a three-month cognitive behavior therapy aimed at reducing stress and after which data was collected through a questionnaire and analyzed using repeated measure analysis of variance. The study revealed that there is reduction in stress level of the Fine and Applied Arts Trainee Instructors who were exposed to cognitive behavior therapy than those that were not exposed to it. It was also observed that men and women respond differently stress and that the presence of stress among Fine and Applied Arts Trainee Instructors limits socio-cultural and economic striving of a state among others. To this effect, the study recommends that Fine and Applied Arts Trainee Instructors at all levels especially in developing countries need to engage on Cognitive Behaviour Therapy (CBT) workshop from to time to time in order to ensure quality service delivery and also for strengthening economy of the state. This research therefore proves that good leadership, educational objective sustainability/viability and zero tolerance of resources/knowledge diversion is achievable if Fine and Applied Arts Trainee Instructors will be exposed to CBT training from time to time.